Izbrana poglavja iz naravoslovnih znanosti – Fizika: Laboratorijske vaje - Krajnc, Borut; Žigart , Marko; Capl, Marjeta; Grubelnik, Vladimir; Marhl, Marko (University of Maribor Press, 2021)
Selected Topics in Natural Sciences - Physics: Laboratory Work.Instructions for laboratory work in the course Selected Chapters from the Natural Sciences - Physics is the result of many years of co-creation and upgrading of natural science content by various authors. The main purpose is to offer concise and transparent material in the field of physical laboratory exercises for students of the Primary teacher programme of the Faculty of Education, University of Maribor. The material is divided into 13 content units, covering all important physical areas from measurements to astronomy. Each unit is broken down with instructions for conducting a number of physical experiments that are directly applicable to science subjects at the elementary school grade level. Those experiments are selected that are instructive and interesting, but at the same time feasible with primary school experimental equipment.